Foundations of Krein Spaces and the Nonequivalence of Pythagorean Orthogonality - Bagas Reynalda; Sisilia Sylviani; Anita Triska (PT Anugrah Teknologi Kecerdasan Buatan, 2026)
This paper presents a fundamental analysis of the Krein Space, which is an indefinite generalization of the Hilbert Space. The Krein Space (K, [·,·]) is equipped with an indefinite inner product [·,·], which satisfies all the properties of a standard inner product except for positive definiteness. The absence of the positive definite property allows for the classification of elements based on their indefinite inner product with themselves into positive, negative, and neutral elements. The Krein space is formally defined through a canonical decomposition K = K+ [Å] K-, where K+ and K- are indefinitely orthogonal subspaces, both of which become Hilbert Spaces after adjusting the sign of their indefinite inner product. This decomposition induces a Canonical Symmetry Operator J, which allows the indefinite inner product to be related to a definite inner product <·,·> through the relation <x,y> = [J x, x]. This relationship defines the induced Hilbert Space norm ll · ll on K, where ll x ll2 = [J x, x]. The main focus of this paper is to demonstrate that indefinite orthogonality in Krein Space fundamentally differs from Hilbert Space orthogonality, particularly concerning the Nonequivalence of the Pythagorean orthogonality.